The Winter's Tale (Colour version)
Colour Directed by Michael Wade. The Company: Mary Lewis, Charlie Tomlinson, Paul Rowe, Stephen McGrath, Janis Spence, Flip Janes, Mercedes Barry, Stephen Lush, Paula Nolan, Bryan Hennessey, Kent Barrett, Frank Barry, Todd O'Brien. Newfoundland Shakespeare Company